Pembelajaran Bermakna Melalui Contextual Teaching And Learning (CTL) Berbantuan Video Animasi untuk Meningkatkan Hasil Belajar IPAS Siswa Sekolah Dasar - Rozanna; Fatimah; Asrul Karim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem underlying this study stems from students’ low IPAS learning outcomes, where the class-wide learning achievement has not yet reached the targets set by the school. In addition, the learning process still tends to be teacher-centered and does not yet utilize learning media capable of connecting the material to students’ real-life experiences. This study aims to describe the implementation of meaningful learning through the Contextual Teaching and Learning model, supported by animated videos, to improve elementary school students’ IPAS learning outcomes. The research method used was Classroom Action Research (CAR), conducted in two cycles in the fifth-grade class at UPTD SD Negeri 4 Bireuen with a sample size of 25 students. Based on the research results, in Cycle I, an average score of 69.2 was obtained with a class-wide mastery rate of 56%, where 14 students were deemed to have mastered the material and 11 students had not. After implementing instructional improvements in Cycle II, the average score increased to 87 with a class-wide mastery rate of 88%, meaning 22 students were deemed to have mastered the material and 3 students had not. In addition, teacher activity increased from 85% to 96%, student activity increased from 84% to 91%, and student response reached 93.81%, falling into the “very good” category. Thus, meaningful learning through the Contextual Teaching and Learning model aided by animated videos can improve elementary school students’ learning outcomes in IPAS.